PEMBIAYAAN EMAS IB HASANAH DAN GADAI EMAS BERDASARKAN PSAK 107 DAN PSAK 102 DI BANK BNI SYARIAH JEMBER - Probowulan, Diyah; Kurniawan, Andrian (Jurnal Ilmiah Akuntansi Indonesia, 2020)
Increasing number of public interest to Islamic banking, Islamic banking requires an accounting standard that differ from conventional banking. Since the Islamic and conventional banking have differences. Islamic banking products and schemes accounting framework requires a thorough transaction to the appropriate accounting measurement produces a rich and allow them to communicate information in a timely manner and reduce the differences in accounting treatment between Islamic banks to one another. Oversight for the accounting treatment of mortgage financing products gold and gold financing Hasanah iB needed, so people will be more convinced that Islamic principles used by the banks. The accounting treatment of gold mortgage products governed by SFAS 107 while the gold financing products iB Hasanah governed by SFAS 102.This study includes a qualitative descriptive study. Data collection was conducted by the author with interviews of employees BNI Syariah branches Jember and use the data in the form of accounting guidelines and ijara and murabaha accounting treatment applied to the mortgage financing products gold and gold financing.The results showed that overall PT Bank BNI Syariah has been running the right and use the accounting guidance of SFAS 107 and SFAS 102 on the scheme for the accounting treatment of transactions and mortgage financing products gold and gold financing iB Hasanah.